ROBIN HIGAHM - THANOS VEREMIS (επιμ.), Aspects of Greece 1936-40: The Metaxas Dictatorship, ELIAMEP-VRYONIS CENTER, 1993, 240 σελ. - Παπαδημητρίου, Δέσποινα (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2017)
Δεν διατίθεται περίληψη / no abstract available